2014
DOI: 10.1647/1082-6742-28.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging of Peripheral Vestibular Disease in a Chinese Goose (Anser cygnoides)

Abstract: A 20-year-old Chinese goose (Anser cygnoides) presented for severe left-sided head tilt and circling to the left. Peripheral vestibular disease associated with otitis media extending into the left quadrate bone was diagnosed by magnetic resonance imaging and computed tomography. Otoscopy confirmed a ruptured tympanic membrane, and a brainstem auditory evoked response test confirmed loss of hearing in the affected ear. Surgery to remove the caseous material and long-term medical therapy improved the bird's head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Magnetic resonance imaging has been proven to be useful to assess chronic sinonasal diseases in psittacine birds, diagnose hydrocephalus in African grey parrots, and has been shown to be superior to radiography in evaluating spinal cord trauma in three bald eagles . Magnetic resonance imaging has been used to diagnose a peripheral nerve sheath tumor in a subadult eagle and peripheral vestibular disease in a Chinese goose . Recently, a pilot study has demonstrated the usefulness of MRI in the detection of brain lesions caused by severe lead poisoning in bald eagles .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging has been proven to be useful to assess chronic sinonasal diseases in psittacine birds, diagnose hydrocephalus in African grey parrots, and has been shown to be superior to radiography in evaluating spinal cord trauma in three bald eagles . Magnetic resonance imaging has been used to diagnose a peripheral nerve sheath tumor in a subadult eagle and peripheral vestibular disease in a Chinese goose . Recently, a pilot study has demonstrated the usefulness of MRI in the detection of brain lesions caused by severe lead poisoning in bald eagles .…”
Section: Introductionmentioning
confidence: 99%
“…Several publications of CT and MRI anatomy in avian species exist. However, those are mainly focused on sinonasal cavities, eyes, head/brain, respiratory tract or spine (de Francisco et al, 2016; Delk et al, 2014; Fleming et al, 2003; Gumpenberger & Henninger, 2001; Gumpenberger & Kolm, 2006; Jones et al, 2019; Krautwald‐Junghanns et al, 1998; Krautwald‐Junghanns et al, 1993; Petnehazy et al, 2012; Pye et al, 2000; Romagnano et al, 1996; Schwarz et al, 2016; Stauber et al, 2007; Verhoye et al, 1998; Wernick et al, 2014) and rarely in the coelomic cavity (Orosz & Toal, 1992; Petnehazy et al, 2012; Romagnano et al, 1996). In the present study, the CT and MRI anatomy of the coelomic cavity in Pekin ducks was provided and corresponding frozen cadaver section photos were provided for CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Once cholesteatoma in the bulla (1) was dissected (2), and all visible disease excised, the inflamed mucosal lining of the bulla is visible (3) with difficulty in finding surgical landmarks 14 and a high risk of complications, 15 and so we have used the endoscope to potentially reduce such risks (video of endoscopic dissection for chronic otitis media in a cat at www.youtube.com/watch?v=t-caPNIgXr&t= 24s). Chronic otitis media has previously been treated surgically in rabbit, 16 alpaca, 17 llama, 18 bison, 19 bongo antelope 20 and goose, 21 and so endoscopic assistance could prove helpful for bulla procedures in a number of species, as well as image guidance when the bulla is difficult to locate. However, we recognise that cost may preclude wider uptake of such systems.…”
Section: Discussionmentioning
confidence: 99%